Tension Pneumothorax Mimicking Acute Myocardial Infarction in a 58-Year-Old Male - Tokdil, Hasan; Raimoğlu, Utku; Soysal, Ali Uğur; İncesu, Gündüz; Ohtaroğlu Tokdil, Kardelen (Cerrahpaşa Medical Journal, 2024)
Cite this article as: Tokdil H, Raimoğlu U, Soysal AU, İncesu G, Ohtaroğlu Tokdil K. Tension pneumothorax mimicking acute myocardial infarction in a 58-year-old male. Cerrahpaşa Med J. 2024;48(3):306-308.